CASE RATE OF ENDARTERITIS AND THROMBOANGITES AMONG THE POPULATION OF DONETSK AND POLTAVA REGIONS - Ishchejkina, Y.A. (World of Medicine and Biology, 2012)
Statistic analysis of a case rate and prevalence of an endarteritis and thromboangiites among the population of some cities and rural districts of Donetsk and Poltava regions over 1980-2008 is realized. Is ascertained that the case rate of the population of endarteritis and thromboangiites are progressively increased throughout 20 years, and rate of increase was especially high in the nineties. The case rates of city and agricultural population are close, and prevalence of this pathology among agricultural population is more. A case rate among men above a case rate of women in 4,7-4,9 times.